2009
DOI: 10.1258/hsmr.2009.009004
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the factors influencing networkability in the health-care sector

Abstract: In most industries of economy, the production structures evolved into activities characterized by a high division of labour between the business partners combined with specialization, the standardization of service components and extensive networking. In the health-care sector, the first signs of a similar development are beginning to crystallize. As a consequence, networkability, the ability to link up with other players on the basis of commonly agreed standards for the joint provisioning of patient-centred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…doctors, pharmacists, nurses) and external stakeholders (patients, governmental agencies, suppliers). The cooperation relationship with suppliers normally is subject to a variety of exogenous and endogenous influencing factors [31] (Figure 2):…”
Section: Cooperation In Health Carementioning
confidence: 99%
“…doctors, pharmacists, nurses) and external stakeholders (patients, governmental agencies, suppliers). The cooperation relationship with suppliers normally is subject to a variety of exogenous and endogenous influencing factors [31] (Figure 2):…”
Section: Cooperation In Health Carementioning
confidence: 99%
“…Inspired by the transformative power of the Web and how -spontaneously or in more organized forms -networked individuals and institutions work together in order to achieve a common goal (Mettler and Rohner 2009), the Competence Center Health Network Engineering (CCHNE) was founded at the Institute of Information Management of the University of St. Gallen with the ambition to connect the diverse stakeholders of the healthcare sector, such as physicians, nurses, concerned citizens, managers and administrators, technology providers for the purpose of jointly solving relevant problems. Since its beginning, the CCHNE systematically makes use of the synergy harnessed from applied, transdisciplinary research in the intersection between management, healthcare, and innovation (see figure).…”
Section: Vision Of the Competence Center Health Network Engineering: mentioning
confidence: 99%
“…Several studies have shown that the successful implementation of e-health services within and across healthcare organizations not only requires the integration of processes, work practices [1,2], and timely and role-specific exchange of information and education [3,4], but also in most cases effective personal interaction between the different actors involved [5][6][7]. This means that prior to deciding about the procurement or development of a new e-health service, the degree of integration between technology and organization, as well as the identification of obstacles and opportunities needs to be analyzed.…”
Section: Introductionmentioning
confidence: 99%